Efficiency and sustainability of microfinance: Study case agribusiness microfinance institutions in Bogor - Triane Widya Anggriani; R. Nunung Nuryartono; Bambang Juanda; Jaenal Effendi (Jurnal Keuangan dan Perbankan, 2019)
Microfinance is one of the solutions in poverty alleviation in rural areas. The existence of financial access in a rural area, with hope, low-income society can increase their revenues and eventually able to escape the circle of poverty. The agribusiness microfinance institution is the institution that provides financing services to farmers in rural areas. However, agribusiness microfinance institution is facing sustainability problems. We analyzed financial sustainability in terms of the cost-efficiency of the Agribusiness Microfinance Institution (AMFI). The study utilized a parametric approach method of Stochastic Frontier Analysis (SFA). The sampling technique used was purposive sampling, namely AMFI possessing two years of financial reports (in the year 2016-2017) around Bogor District, there were fifteen AMFIs qualified. The result indicates AMFIs' efficiency value in Bogor District almost approaching 100%. It means that the AMFIs' financial performance in Bogor District was highly efficient. Labor cost is a very responsive variable in the total cost. However, AMFIs' labor cost was low. This matter caused administrator performance in servicing their customers to become not optimal, thus impacting the unsustainability of AMFI.JEL Classification: G21, G23DOI: https://doi.org/10.26905/jkdp.v23i4.3591